Supporting care engagement in primary care; the development of a maturity matrix - Wolters, René; Mokadem, Ibtissam; Wensing, Michel; Braspenning, Johanna Catharina Cornelia (PLOS ONE, 2023)
Care engagement or active patient involvement in healthcare contributes to the quality of primary care, but organisational preconditions in routine practice need to be aligned. A Maturity Matrix for Care Engagement to assess and discuss these preconditions in the general practice team was developed and tested on feasibility and acceptability in general practice. Methods and findings A systematic user-centred approach was applied, starting with a scoping literature search to describe the domains on the horizontal axis of the maturity matrix. The domains and growing steps (vertical axis) were refined by patients (n = 16) and general practice staff (n = 11) in three focus group discussions and reviewed by six experts (local facilitators and scientists). ...
Gesehen am 07.12.2023